ANTIMICROBIAL ACTIVITIES OF EXTRACTS OF SOME PLANTS - Kirbag, Sevda; Zengin, Fikriye; Kursat, Murat (Pakistan Botanical Soc, 2009)
In this study, the antimicrobial activity of Myricaria germanica (L.) Desv., Centaurium erythraea Rafn subsp. turcicum (Velen.) Melderis, Prunella vulgaris L., Pelargonium endlicherianum Fenzl., Chrysophthalmum montanum (DC) Boiss. and Jurinea ancyrensis Bornm., were investigated. The antimicrobial activity were evaluated according to the disk diffusion method by using Bacillus megaterium DMS 32, Pseudomonas aeruginosa DMS 50071 SCOTTA, Escherichia coli ATCC 25922, Klebsiella pneumoniae FMC 5, Proteus vulgaris FMC 1, Staphylococcus aureus COWAN 1 FMC 16, Candida albicans FMC 17, Candida glabrata ATCC 66032 and Candida tropicalis ATCC 13803 In the end of experimental studies, the extracts of six plants used in this study were inhibited the growth of microorganisms used in the test at different ration. The results indicated that Chryosphtalum montanum had the greatest antimicrobal activity.
Keywords: Medicinal-Plants; Antibacterial